2000
DOI: 10.1121/1.428345
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic X-wave reflection and transmission at a planar interface: Spectral analysis

Abstract: The spectral structure of a three-dimensional X-wave pulse incident on a planar surface of discontinuity is examined. Introducing a novel superposition of azimuthally dependent pulsed plane waves, it is shown for oblique incidence that the reflected pulse has a localized wave structure. On the other hand, the transmitted field maintains its localization up to a certain distance from the interface, beyond which it starts disintegrating. An estimate of the localization range of the transmitted pulse is establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…In the third paper, the authors investigated the case of a three-dimensional acoustical X-wave. They demonstrated that the transmitted field loses its LW structure; however, it stays localized for a certain distance before it starts disintegrating [16]. Furthermore, they were able to deduce an expression for the dispersion-free range and confirm numerically that such an estimate is consistent with the decay pattern of the transmitted field.…”
Section: Introductionmentioning
confidence: 67%
See 4 more Smart Citations
“…In the third paper, the authors investigated the case of a three-dimensional acoustical X-wave. They demonstrated that the transmitted field loses its LW structure; however, it stays localized for a certain distance before it starts disintegrating [16]. Furthermore, they were able to deduce an expression for the dispersion-free range and confirm numerically that such an estimate is consistent with the decay pattern of the transmitted field.…”
Section: Introductionmentioning
confidence: 67%
“…17] must be rotated by an angle equal to the angle of incidence. Following a procedure introduced for acoustical X-waves incident on a discontinuity surface [16], we transform the Fourier spectral superposition of the electromagnetic X-wave into an azimuthally dependent angular representation [cf. Eq.…”
Section: The Spectral Composition Of the Incident Reflected And Tranmentioning
confidence: 99%
See 3 more Smart Citations